2021
DOI: 10.1021/acs.macromol.1c00546
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization and Depolymerization of Photoluminescent Polyarylene Chalcogenides

Abstract: Engineering thermoplastics feature high chemical, mechanical, and thermal robustness but often lack advanced functionalities as a result of the harsh conditions required for their synthesis and processing. Herein, we introduce a series of polyarylene chalcogenides (PACs), a classification which encompasses polyphenylene sulfides, polyphenylene oxides, and their derivatives, obtained via the room-temperature polymerization of difluorophthalonitrile and disilyl­(thio)­ether monomers in the presence of fluoride o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…PMDI-X2 monomers were homocoupled to polymeric and oligomeric polyphenylenes, linked directly through the PMDI core benzene rings, albeit via Yamamoto or Ullman homocoupling as opposed to SNAr. 12 Recently Swager et al 13 demonstrated the SNAr copolymerization of dihalo phthalonitriles as electrophiles and TMS-protected dithiolates as nucleophiles to produce poly(arylene sulfide)s (PAS). The latter nucleophiles had been demonstrated as effective alternatives to dithiolates in their SNAr copolymerization with perfluoroaromatics as electrophiles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PMDI-X2 monomers were homocoupled to polymeric and oligomeric polyphenylenes, linked directly through the PMDI core benzene rings, albeit via Yamamoto or Ullman homocoupling as opposed to SNAr. 12 Recently Swager et al 13 demonstrated the SNAr copolymerization of dihalo phthalonitriles as electrophiles and TMS-protected dithiolates as nucleophiles to produce poly(arylene sulfide)s (PAS). The latter nucleophiles had been demonstrated as effective alternatives to dithiolates in their SNAr copolymerization with perfluoroaromatics as electrophiles.…”
Section: Introductionmentioning
confidence: 99%
“…The latter nucleophiles had been demonstrated as effective alternatives to dithiolates in their SNAr copolymerization with perfluoroaromatics as electrophiles 14 . Swager et al 13 went further to exploit the pseudo‐degenerate ipso ‐substitution 15 of thiolate leaving groups with other thiolates to depolymerize PAS's with small‐molecule thiols as chain limiters and using only a catalytic amount DBU as base at room temperature! This facile reaction under mild conditions with PASs carrying activating electron‐withdrawing groups stands in stark contrast to the cleavage of unactivated and weakly activated diaryl sulfides requiring substantially more forcing conditions (e.g., ≥120°C) 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using disilyl thioethers as monomers, they have been able to prepare new poly(arylene sulfide)s under mild conditions that incorporate advanced functions such as photoluminescence and redox responsiveness and, moreover, can be easily degraded. 7 While several sulfur-containing porous materials have been reported in the literature, 8 examples of porous materials containing aryl thioether linkages in the backbone are extremely scarce. 9 Swager and co-workers reported the synthesis of thianthrene-based 2D polymers with high surface areas and interesting redox properties by using dynamic S N Ar reactions of thiocatechols and perfluorinated aromatic compounds ( Scheme 1 b).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, significant efforts by the Swager group have been directed toward the synthesis of functional PPS analogues. By using disilyl thioethers as monomers, they have been able to prepare new poly­(arylene sulfide)­s under mild conditions that incorporate advanced functions such as photoluminescence and redox responsiveness and, moreover, can be easily degraded . While several sulfur-containing porous materials have been reported in the literature, examples of porous materials containing aryl thioether linkages in the backbone are extremely scarce .…”
Section: Introductionmentioning
confidence: 99%